UNIVERSALISME ISLAM DAN KOSMOPOLITISME PERADABAN - Rosmala Dewi (Nurani, 2015)
Abstrak: Islam is a universal religion, the religion that its enforcement is not limited by space and time. He is fit for the entire human race. Universality of Islam first of all looks at the concept of monotheism into joint doctrine. Islam does not distinguish skin, language, race, rank, degree. ملخص:الإسلام ھو دین عالمي، دین أن تنفیذه لا یقتصر بواسطة الفضاء والوقت .انھ یصلح لجمیع الجنس البشري .عالمیة الإسلام أولا وقبل كل نظرة في مفھوم التوحید في العقیدة المشتركة .الإسلام لا یمیز اللون أو اللغة أو العرق أو رتبة، درجة. Kata Kunci: univeralisme, kosmopolitisme